Changes in some serum hormonal profiles during pregnancy in single- and twin foetus-bearing Akkaraman sheep - Yildiz, A; Balikci, E; Gurdogan, F (Polish Soc Veterinary Sciences Editorial Office, 2005)
This study was conducted to determine the changes in the blood serum concentrations of T-3, T-4, TSH, E-2 and P-4 hormones at days 60, 100 and 150 of gestation in single- and twin foetus-bearing Akkaraman sheep. Serum P-4 and E-2 concentrations (on day 150) significantly increased (P < 0.001); meanwhile there were significant decreases (P < 0.05) in T-4 and insignificant decreases in T-3 (P > 0.05) while there were no significant changes in TSH during the sheep's pregnancy. Results of the tests of the twin pregnancy revealed a significant increase (P < 0.001) in P-4 and E-2 while there was a significant decrease (P < 0.05) in T-3 and T-4 when compared to the single bearing sheep. It may be concluded that the number of foetuses significantly influences the hormone profile during pregnancy. Predicting single or twin pregnancies in sheep is possible when basing on P-4 values and taking into account the time of mating.
Keywords: oestradiol; progesterone; thyroid hormones; sheep; pregnancy